Manajemen Peningkatan Mutu Pendidik PAUD Formal (Studi Kasus Pada Dinas Pendidikan Kota Subulussalam) - Aryawan Bancin (UMSU, 2023)
This research aims to find out how planning, implementation and control are carried out in improving the quality of Formal PAUD educators in Subulussalam City. This research uses a qualitative approach, with descriptive qualitative type. The research location is Subulussalam City, with the main research subjects being the Head of the Service, Head of PAUD and DIKMAS Fields, Head of IGTKI Subulussalam City, Teachers and Parents of students. Meanwhile, data collection techniques used observation, interviews and documentation techniques, then data analysis techniques were carried out in stages, namely data reduction, data presentation, and drawing conclusions. Research results include; 1) Planning to improve the quality of Formal PAUD educators in Subulussalam City is oriented towards improving the achievement of educator standards ideally, with a program to encourage the improvement of teacher education qualifications to the S-1 level through bachelor/linear. Planning on increasing teacher competency capacity, through tiered education and training programs, technical guidance activities, career advancement training and similar development. From the results of the plan to improve the quality of educators carried out by the Education and Culture Office of the City of Subulussalam in accordance with the qualification and competency standards suggested by the government by encouraging subsidized education funds and self-help. 2) Implementation of improving the quality of educators organized by the Office of Education and Culture of the City of Subulussalam which is adjusted to regulations and planning agendas that have been prepared such as tiered training, technical guidance activities, career advancement training and other developments in accordance with regional capabilities and received in allocating the activity budget improving the quality of educators in Subulussalam City. 3) Controlling the improvement of the quality of Formal PAUD educators in Subulussalam City by implementing standard referral stages while still cooperating with official institutional instruments such as the Aceh BPMP and applicable law rules.